Rare case of pseudogout in the scapular region - Andrews, Zenina Reuben; Mohanapriya, T.; Singh, K. Balaji (International Surgery Journal, 2019)
Calcium pyrophosphate dihydrate crystal deposition disease (CPPD) also referred to as pseudogout is an inflammatory arthritis produced by the deposition of calcium pyrophosphate crystals in the synovium and periarticular soft tissues. This report documents a case of a 41 year old female who presented with a painful swelling in the back. MRI revealed a complex swelling with lobulation of size 7.4×7.4×7 cm in the posterolateral aspect of chest wall just superficial to the ribcage. A surgical excision biopsy of the swelling was done and patient improved symptomatically. Serum uric acid levels were measured and found to be within limits.